Predictive Value of Some Central Obesity Anthropometric Indicators to Metabolic Risk Factors in Syrian Adolescents - Al-Bachir, Mahfouz; Adel Bakir, M (Journal of Biotechnology and Biomedical Science, 2018)
Obesity has become a serious health issue worldwide. There is much evidence that obesity among adolescents contributed to worsening blood biochemical profile that leads to development of many non-communicable diseases. Therefore, the aim of this study was to evaluate the predictive value of some central obesity anthropometric indicators to metabolic risk factors in the Syrian male adolescents. A cross-sectional study of a randomly selected sample of 2064 apparently healthy Syrian males’ adolescents from Damascus city, Syria, aged 18 to 19 years was performed. Waist circumference (WC) and hip circumference (HC) were measured, and waist-to-hip ratio (WHpR) and waist-to-height ratio (WHtR) were calculated. Blood pressure (BP) was also measured. Serum fasting blood sugar (FBS), triglyceride (TG), low-density lipoprotein cholesterol(LDL-C), total cholesterol (Chol) were determined. The metabolic risk factors components were defined according to the national criterion. A receiver operating characteristics (ROC) curves were drawn to determine appropriate cut-off points of the WC, HC, WHpR and WHtR for defining the performance of these measurements as predictors of metabolic risk factors. The obtained data showed that BP and overall concentrations of TG, Chol and TG/HDL were significantly (p<0.05) increased with increasing WC, HC, WHpR and WHtR values. Based on ROC calculation for the measured anthropometric indicators and some metabolic syndrome (MetS) risk factors, the best WC HC, WHpR, WHtR cut-offs values were ranged between 73.15 - 79.90 cm, 93.75 - 101.10 cm, 0.80 - 0.81, and 0.43 and 0.47, respectively. These cut-off values were lower than the values recommended by the WHO. In conclusion: A significant association between the studied anthropometric indicators and the MetS components has been demonstrated. The best cut-offs of these indicators were defined. These cut-off values were lower than the values recommended by the WHO. Our results indicating that WC, WHpR and WHtR could be better predictors of MetS risk factors in Syrian adolescents.
Keywords: Anthropometric indicators; Obesity; Risk factor; Waist circumfeence; Syrian adolescents.